Karakter Tanaman yang Mempengaruhi Hasil Tanaman Jarak Pagar (Jatropha curcas L.) - ., Djumali; Nurnasari, Elda (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACT Yield variety of physic nut is one of the factor that cause the gap between the potential and actual yields. In a homogeneous environment, plant yield is controlled by multigenes. To obtain a homogeneous yield, it is necessary to determine the plant characters affecting physic nut yield. A research was carried out in Asembagus and Muktiharjo Research Stations in January-December 2010 to observe plant growth and yield of IP-3A and IP-3M genotypes. Data were analyzed backward stepwise to determine the plant characters that affect plant yield. The results showed that IP-3A plant characters affecting yield from the greatest were the number of branches, the ratio C / N in petiol, the number of non-productive branches, the amount of glucose needed to form per gram petiol tissue, C-organic content in petiol, the ratio C / N in stem, C-organic content in stem, and the amount of glucose needed to form per gram stem tissue. Of the eight characters, only the number of non-productive branches negatively affected on yield, while other characters showed positive influence. The IP-3M plant characters affecting yield from the greatest were the ratio C / N in shoot, N content in shoot, the amount of glucose needed to form per gram shoot and stem tissues, C-organic content in shoot and stem, the amount of glucose needed to form per gram leaf tissue, C-organic content in leaf and water content in stem. Of the nine characters, only the N content in shoot that negatively affected on plant yield, while other characters showed positive influence.Keywords: character, growth, Jatropha curcas, productive branches, yield